UPAYA MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR MELALUI PENERAPAN MODEL PROBLEM BASED LEARNING PADA SISWA KELAS XI MIPA 8 SMA NEGERI 7 DENPASAR TAHUN PELAJARAN 2020/2021 (LP3M Universitas PGRI Mahadewa Indonesia, 2021)
The purpose of this study was to determine the increase in activity, learning achievement, and student responses of class XI MIPA 8 to the application of problem-based learning models in mathematics learning. This type of research is a classroom action research conducted online via Zoom and Google Classroom. The research subjects were all students of class XI MIPA 8 at SMA Negeri 7 Denpasar in the academic year 2020/2021 even semester, totaling 40 people. This study uses two cycles to improve students' mathematics learning outcomes through four stages of the activity process which includes: planning, action, observation, evaluation and reflection. Data collection techniques in this study are using test and observation methods. The results showed (1) The application of the problem based learning model can increase students' mathematics learning activities. (2) The application of the problem based learning model can improve students' mathematics learning achievement. (3) There is a very positive response from class XI MIPA 8 students to the application of the problem based learning model in mathematics learning.